Intelligent user interfaces : adaptation and personalization systems and technologies - Mourlas, Constantinos; Germanakos, Panagiotis (Hershey, PA : Information Science Reference, 2009)
'This book identifies solutions and suggestions for the design and development of adaptive applications and systems that provides more usable and qualitative content and services adjusted to the needs and requirements of the various users'--Provided by publisher
Includes bibliographical references and index
Keywords: Human-computer interaction; Artificial intelligence; Adaptive computing systems